Highly polymorphic XbaI RFLPs of the human 21-hydroxylase genes among Chinese. Issue 4 (April 1992) - Chen, L; Pan, X; Shen, Y; Chen, Z; Zhang, Y; Chen, R
Abstract : A highly polymorphic XbaI restriction site flanking the human 21-hydroxylase genes (21-OHA and 21-OHB) was found with the probe pC21/3c, the cDNA of the 21-hydroxylase gene. From the results of RFLP analysis of 10 subjects with congenital adrenal hyperplasia (CAH) owing to 21-hydroxylase deficiency and their parents, at least four polymorphic fragments (30 kb, 27 kb, 25 kb, and 15 kb) resulting from cleavage at the polymorphic endonuclease sites outside the genes were found, and at least 10 different polymorphic patterns were observed among Chinese. These results indicate that these polymorphic loci are very informative for prenatal diagnosis of 21-hydroxylase deficiency.